Ilmu Ladunni dalam Perspektif al-Ghazali - Agus Sutiyono (Nadwa: Jurnal Pendidikan Islam, 2013)
Science Ladunni inspiration is flowing light, which can occur after improvement (taswiyah). Rationally, all knowledge can be acquired through learning. This is key in pursuing the  events and education trips. Learning becomes importantwhen one wants to reach the succes top life in understanding the science. How to get the science ladunni according to al-Ghazali, namely; first, trying to grab all the knowledge and take the highest ration of science the most. Second, proper training (ar-riyad ash sad iqah) and supervision are valid (al-muraqabah as sahihah), and still a fraid God with truth. Third, thinking (tafakur), if the soul has learned and trained to be a science, then he bertafakur. Fourth rabbaniyah purify hearts decorated with zikrullah.AbstrakIlmu Ladunni ialah mengalirnya cahaya ilham, yang bisa terjadi setelah penyempurnaan (taswiyah). Secara rasional, semua ilmu pengetahuan dapat diperoleh melalui belajar. Ini merupakan kunci dalam meniti peristiwa dan perjalanan pendidikan. Belajar menjadi penting Ketika seseorang ingin mencapai puncakkeberhasilan hidupnya dalam memahami ilmu. Cara  mendapatkan ilmu ladunni menurutt al-Ghazali yaitu; pertama, berusaha meraih semua ilmu dan mengambil jatah terbanyak dari ilmu yang paling banyak. Kedua, latihan yang benar ( ar-riyad}ah as}-s}adiqah ) dan pengawasan yang sahih ( al-muraqabah as}-s}ahihah ), serta tetap merasa takut kepada Allah dengan sebenar-benarnya. Ketiga, berfikir (tafakur), apabila jiwa telah belajar dan terlatih akan suatu ilmu, kemudian iabertafakur. Keempat mensucikan hati  rabbaniyah yang dihiasi dengan  z\ikrullah .